The Curse of the Nine-Banded Armadillo: Case Report and Review. Issue 7 (1st July 2015) - Elsayed, Galal; Elsayed, Mohammed; Clincea, Radu; Talley, James; Ignacio, Melissa; Thompson, Jennifer C.
ABSTRACT: Hansen's disease (leprosy) is an ancient condition characterized by hypopigmented patches that progress to become plaques with hypoesthesia. Several case reports suggest that armadillos may be a source of Mycobacterium leprae for clinical cases, and contact with armadillos has been shown to be a significant risk factor in several case-control studies. Early diagnosis and treatment result in an excellent prognosis and provide an effective means to prevent complications of peripheral nerve injury, social stigma, and disability. We present a case of Hansen's disease in a previously healthy veteran and provide an overview of the diagnosis, classification, and treatment of the condition. Clinicians should consider leprosy in the differential diagnosis when confronted with chronic skin lesions in the appropriate clinical setting.